DISPOSAL PRACTICE OF BRICK KLIN WASTE THROUGH STABILIZATION OF FINE GRAINED SOILS- A REVIEW - Mirza, Mohammad Iqbal (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Brick klin waste (BKW) is a byproduct generated during the manufacture of bricks in traditional brick klins. Its improper disposal results in environmen- tal deterioration and health hazards. In recent times, engineers and researchers have explored soil stabilization as a sustainable and eco-friendly avenue to man- age and utilize BKW. This approach has a two-fold advantage: one to get rid of the tremendous environmental issues associated with indiscriminate dumping of BKW occupying valuable land, and a second to minimize the stabilization cost of soft or marginal soils. This review assesses the effectiveness, environmen- tal impact, and potential applications of brick klin waste in soil stabilization of clayey geomaterials. The outcomes depict that most of the physical, chemical, mineralogical, toxicity, microstructural, and geotechnical characteristics of BKW are in the range of other geomaterials. It is established that incorporating BKW in soft soils in certain percentages improves their strength and stability char- acteristics significantly. According to many researchers, the blended mixture of BKW and fine grained soils attain better gradation features, more volume stabil- ity, enhanced bearing capacity, and a higher California bearing ratio (CBR). As such, BKW alone or replacing a certain percentage in soft soils finds its scope in the different applications of geotechnical engineering. Additionally, it can result in its mass consumption and an improvement in the soil properties in a much more sustainable and economical manner.